Pendekatan Burhani sebagai Fondasi Rasional dalam Analisis Wacana Ilmiah Islam - Nugraha, Aszahra Regita; Faradisa, Amirah; Maulidyah, Shandy; Hastin, Nisrina Nurlaela Yumna; Auliza, Viranda Rizky; Aulia, Izza Asti; Kurniawan, Taufiq (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Islam has a comprehensive epistemology as the primary foundation for acquiring knowledge. In general, epistemology in Islam exhibits three strong tendencies: bayani, irfani, and burhani. These three forms of reasoning originate from the thoughts of Muhammad Abid al-Jabiri, a contemporary Moroccan philosopher known for his efforts to develop a philosophy that combines rationality, authority, and intuition. According to al-Jabiri, these three forms of reasoning serve not only as tools for acquiring knowledge but also as a way to understand the relationship between humans and God, nature, and themselves. Bayani epistemology emphasizes the study of texts (nas), ijma, and ijtihad as basic references for justifying certain beliefs. This study summarizes the concept that burhani epistemology emphasizes the innate human potential in terms of intuition, senses, experimentation, and conceptualization, expressed as "al-hiss, al-tajribah wa muhakamah 'aqliyah." Bayani reasoning, which focuses on authoritative texts, is used to understand revelation and religious teachings, while irfani reasoning explores deeper dimensions of knowledge through inner experience and mystical intuition. By combining these three types of reasoning, a complete Islamic science will emerge that is able to solve contemporary social problems in the development of Islam. This study was conducted with a qualitative approach using text analysis methods that aim to explore the concepts proposed by al-Jabiri in his work and relate them to epistemological theories that have been introduced in the Islamic philosophical tradition. From the specific analysis, it was found that al-Jabiri considered these three forms of reasoning to be complementary, not contradictory, in an effort to achieve a more comprehensive and holistic understanding of reality.